Efficiency comparison of online and offline markets: evidence from the two largest U.S. retailers - Paskert, Niklas (University of Cape Town, 2020)
The online market has developed into an equally strong competitor to the offline market. This study examines the market efficiency of the U.S. online and offline market based on the price level, price dispersion, price elasticity and menu cost. A direct comparison of all four market efficiency criteria based on empirical results is not discussed in the literature. Here, the empirical study analyzes and compares the online and offline prices of electronic products between the two largest retailers, Amazon and Walmart. The results clearly indicate that the online market is more efficient than the offline market. Comparing the online prices between the multichannel retailer Walmart and the pure online retailer Amazon we find that for 64.5% of the electronic products, Amazon has the better offer. While 26% of the prices are identical and only 9.5% of the overall prices offered by Walmart are lower. The price advantage of Amazon is explained by the strong price linkage between the online shop and the less efficient offline shop within the retailer Walmart. In 73% of the examined prices, the online and offline prices at Walmart are identical. Furthermore, this price linkage causes a high price dispersion of 14.7% between the online shops of the two retailers. As soon as Walmart breaks the price linkage through sales offers in their online shop, the price dispersion between the two retailers drops to 10.2%.